2019
DOI: 10.1063/1.5064392
|View full text |Cite
|
Sign up to set email alerts
|

Verification of azimuthal current generation employing a rotating magnetic field plasma acceleration method in an open magnetic field configuration

Abstract: Time-varying, azimuthal electron current is obtained from measured two-dimensional profiles of excited magnetic fields, using the Rotating Magnetic Field (RMF) plasma acceleration method in an open magnetic field configuration. The RMF is applied orthogonally to cylindrical plasma, leading to the azimuthal current drive via the Hall effect. Here, dc azimuthal current, whose magnitude is equivalent to that of ac azimuthal current with twice the RMF frequency, is verified for the first time. In addition, an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To this point, Furukawa's group performed azimuthal plasma current measurements directly in an RMF thruster. They showed that azimuthal currents are indeed induced by the RMF but at ∼2.5% of the theoretically expected value [17]. In our recently developed test article, the RMF magnitudes are higher and frequencies are lower, and therefore we expect a more effective RMF current drive owing to increased field penetration into the plasma.…”
Section: Introductionmentioning
confidence: 60%
“…To this point, Furukawa's group performed azimuthal plasma current measurements directly in an RMF thruster. They showed that azimuthal currents are indeed induced by the RMF but at ∼2.5% of the theoretically expected value [17]. In our recently developed test article, the RMF magnitudes are higher and frequencies are lower, and therefore we expect a more effective RMF current drive owing to increased field penetration into the plasma.…”
Section: Introductionmentioning
confidence: 60%
“…Mathematical Sciences Northwest (MSNW) developed multiple test articles demonstrating pulse energies up to 50 J on gases including nitrogen and xenon [5][6][7][8]. Tokyo University of Agriculture and Technology implemented another RMF device intended to run semi-continuously at 1 kW on argon [9,10]. At the University of Michigan, we recently built and characterized a test article that demonstrated steady-state operation at 150 pulses per second and powers up to 4.5 kW operating on xenon.…”
Section: Introductionmentioning
confidence: 99%
“…With that said, there is a lack of direct experimental data to assess what drives the efficiency loss. Moreover, for the data that has been previously generated, either the diagnostics had limited accessibility [9,10] or the test articles in question were operated in facilities that were not representative of the on-orbit environment where these devices are intended to operate [5][6][7][8]. Given the outstanding fundamental questions about the operation of RMF thrusters, there is an apparent need for a detailed experimental characterization of the efficiency modes of the performance of an RMF device operating under more space-like conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,5 Not surprisingly, exploration of new physical principles for creating thrust in space, 6,7 and advanced implementation of the existing thrust systems attract strong attention of the researchers. 8,9 Among other space propulsion systems, the thrust platforms that utilize plasma 10 , 11, -12, 13 and ionized gas 14,15,16 to create reactive thrust are currently attracting the strongest attention due to many potential advantages of these devices, 17,18,19 mainly owing to very high specific impulse 20,21 and potentially long service life. 22,23 However, further uptake of these systems is challenged by several problems.…”
Section: Introductionmentioning
confidence: 99%